Inhibition of COX‐2 Pathway as a Potential Prophylaxis Against Arthrofibrogenesis in a Rabbit Model of Joint Contracture. Issue 12 (26th August 2019) - Salib, Christopher G.; Reina, Nicolas; Trousdale, William H.; Limberg, Afton K.; Tibbo, Megan E.; Jay, Anthony G.; Robin, Joseph X.; Turner, Travis W.; Jones, Carter R.; Paradise, Christopher R.; Lewallen, Eric A.; Bolon, Brad; et al.
Abstract : Arthrofibrosis is a common complication following total knee arthroplasty resulting in debilitating loss of motion. We explored the novel use of celecoxib (selective cyclooxygenase‐2 [COX‐2] inhibitor) to disrupt the downstream effects of the post‐traumatic inflammatory cascade and inhibit scar tissue formation in a validated rabbit model of arthrofibrosis. Biomechanical, molecular, and histologic analyses of contracted rabbit knee posterior capsule tissue after COX‐2 inhibition revealed down‐regulation of collagen messenger RNA, and increased maximal passive extension compared with controls. ABSTRACT: Arthrofibrosis is a common complication following total knee arthroplasty caused by pathologic fibroblast activation and excessive collagen deposition around a synovial joint leading to debilitating loss of motion. Treatment options are limited because the pathologic mechanisms remain to be characterized. Dysregulation of the inflammatory cascade may lead to communication between myofibroblasts and immune cells triggering tissue metaplasia, and excessive collagen deposition described clinically as arthrofibrosis. We explored the novel use of celecoxib (selective cyclooxygenase‐2 [COX‐2] inhibitor) to disrupt the downstream effects of the post‐traumatic inflammatory cascade and inhibit scar tissue formation in a validated rabbit model of arthrofibrosis combined with new parameters for quantifying the stiffness of the posterior capsule. Biomechanical and molecular analyses, of contracted rabbit knee posterior capsule tissue after COX‐2 inhibition revealed increased maximal passive extension and down‐regulation of collagen messenger RNA compared with controls. Histopathologic examination suggested a trend of decreased quantities of dense fibrous connective tissue with COX‐2 inhibition. These data may suggest that inhibiting the inflammatory cascade could potentially reduce pathologic myofibroblast activation, thereby reducing scar tissue formation and increasing the range of motion in arthrofibrotic joints. Implementing a multi‐modal pharmacologic approach may simultaneously target numerous cellular components contributing to the complex process of arthrofibrogenesis. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 37:2609–2620, 2019